المشكلات اللغوية في الترجمة (بحث بالجامعة الإسلامية الحكومية فونوروغو) - ألباء الحسنى (Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2017)
This article tries to find the linguistic problems in translation faced by Arabic students of STAIN Ponorogo, both in translating Arabic text to Indonesian language and Indonesian text to Arabic language. By error analysis of the daily tasks of students and answer sheets of translation exam, the writer find that the problem of translation in Arabic text to Indonesian language can be clasificacied in to three categories, 1) Vocabulary, 2) sentence arrangement, and 3) grammar. And for translating Indonesian text to arabic, there are four categories of errors, 1) vocabulary, 2) grammar, 3) vocabulary, and 4) transliteration. Keywords: linguistic problems, translation